AN ANALYSIS OF CODE SWITCHING IN THE NOVEL JENDELA-JENDELA BY FIRA BASUKI - Leny Krismayanty, - (2005)
This study investigates the use and the function of code switching performed by the characters in the novel entitled Jendela-Jendela written by Fira Basuki, To investigate the phenomenon, the descriptive method is used. The data were collected from novel which associated with code switching performed by the characters. The data were classified based on its syntactic categories, type, and function of code switching. Furthermore, occurrences of code switching in each category were identified, and their percentages were calculated for further accounts of the data. Interpretations were made on tendencies that appeared from the quantification. There were several findings found in this study. First, based on its syntactic categories, the code switching performed by the characters in the novel is found in the level of word, phrase, and clause. Second, code switching which is transformed into the syntax of the main language mostly occurred at the phrase level. All of the phrases stick to Indonesian syntactic categories. Third, there were two types of code switching found in the novel; those are intra sentential and inter sentential. Fourth, the function of code switching performed by the characters in the novel are giving emphasis, untranslatability, personalization, designation, clarification, quotation, interjection, and reiteration. In the end, it can be concluded that the phenomenon of the use of code switching performed by the characters in this novel is influenced by the author's background who is bilingual and the setting of the story itself which involves different places, namely Indonesia, Singapore, and United States.